2013
DOI: 10.1371/journal.pone.0074018
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Characterization of Circulating Respiratory Syncytial Virus (RSV) Genotypes in Gilgit Baltistan Province of Pakistan during 2011-2012 Winter Season

Abstract: Respiratory syncytial virus (RSV) is the major cause of acute lower respiratory tract infections in young children, but very little is known about its epidemiology and circulating genotypes in Pakistan. This study analyzed the epidemiological and molecular characteristics of RSV genotypes detected in Pakistani children less than 2 years of age with acute respiratory tract infections (ARIs) in a tertiary care hospital in Gilgit Baltistan (GB) province during 2011-12 winter season. RSV was detected in 75 out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…Earlier studies have reported maximum number of cases of RSV in children less than 2 years of age [45,57,58]. Maximum number of cases were recruited in 0–6 months in the present investigation that coincides with higher percentage of RSV infection in this age group as reported earlier [57].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Earlier studies have reported maximum number of cases of RSV in children less than 2 years of age [45,57,58]. Maximum number of cases were recruited in 0–6 months in the present investigation that coincides with higher percentage of RSV infection in this age group as reported earlier [57].…”
Section: Discussionsupporting
confidence: 83%
“…Further, more number of male cases with RSV infection were observed as compared to the females that is due to the fact that more number of male patients were recruited in the study. Higher percentage of RSV infection in male children has been reported earlier also [5,57]. Fever and nasal discharge were the most common clinical symptoms observed among the patients.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The second HVR (HVR2) carries the C terminus of the protein and is commonly sequenced to exam the genetic variability of RSV strains within a given population (Da Silva et al 2008). National (Da Silva et al 2008) and international (Aamir et al 2013, Entemadi et al 2013) researches aimed to correlate epidemiological and clinical aspects of different groups (A or B) and several genotypes of RSV. They found variation by local research center and by current genotypes distribution.…”
Section: The Discoverymentioning
confidence: 99%